Assessment of Air Quality Conditions in an Area in the Gulf of Guinea, Ibadan, Using Low-Cost Sensors (2025)
Air quality monitoring is essential for the determination of the potentialnegative impacts of air pollution on humans and the environment. This study investigated the contribution of particulate matter (PM 2.5 and 10) to air quality in an area in the Gulf of Guinea, far south of Sahara. The study used the hourly data of PM 2.5 and 10 concentrations and other auxiliary data in 2021 from the PurpleAir sensors. These PM concentration data were first converted into Air Quality Index (AQI) using appropriate method of aggregation. Subsequently, the AQI was used to categorize the ambient air into six classes that range between “Good" to "Severe" conditions. Results indicated higher prevalence of "Good “to “Satisfactory" AQI conditions during the peak of the rainy season (June, July and August), characterized by low PM concentrations, whereas the harmattan season (December, January and February) exhibited a higher prevalence of "Very Poor" to "Severe" conditions, characterized by high PM concentrations. High AQI and PM concentrations were attributable to organic PM Saharan dust in the harmattan season, while low AQI and PM concentrations in the rainy season were associated with localized anthropogenic sources. Thus, the low-cost sensor PurpleAir was able to capture the expected seasonal patterns peculiar to the study region.